Les infographies de presse à l’école : des effets de contextes à travers une étude socio-didactique comparatiste - Jacques Kerneis; Jérôme Santini (Recherches en Éducation)
This article brings out the semiotic, enunciative and epistemic specificities of infographics and their ability to produce differences between students. First, we analyze two infographics dealing with household consumption. Then we analyse a priori two sequences in which both infographics are presented, in a comparative and contrastive way. These teaching sequences were produced eight years apart; the first one was produced during the middle school (grade 9) whereas the second one was produced during vocational school. The article attempts to demonstrate how the way we conceive a sequence can either aggravate inequalities between pupils or be a source of emancipation for all. This is achieved through an approach articulating joint action theory in didactics, the didactic of contexts and sociology. The study seems to be relevant at a time where media and information education is included the reformulation law of July 2013 and in the 2014 project on the knowledge skills and culture base.